Natural disasters and high-stakes exam performance: Evidence from the 2008 Wenchuan earthquake - Wei Lu; Yang, Po; Shilin Zheng; Sen Zhou (China Economic Review, 2023)
In this study, the 2008 earthquake in Wenchuan, China serves as a natural experiment for examining the effect of natural disasters on high-stakes exam performance among students who were admitted to four-year colleges between 2005 and 2011. Results of a generalized difference-in-differences model show that, on average, the earthquake reduced a student's National College Entrance Examination (NCEE) standard score by 55% of a standard deviation. The findings have implications for higher education and China's economy, because earthquake exposure lowers a student's probability of being accepted to an elite college, pursuing a major in a high-salary field, and moving to a highly developed urban area for education or employment.
Keywords: Academic achievement; Earthquakes; High-stakes exams; Natural disasters